The Calculation of Inverse Kinematics for 6DOF Serial Robot - Uricek, Juraj; Galbavy, Tibor; Bulej, Vladimir; Durec, Peter (Communications - Scientific letters of the University of Zilina, 2014)
This article deals with the inverse kinematic model of robot devices which was implemented into the simulation software RoboSim designed at the Department of Automation and Production Systems – Faculty of Mechanical Engineering, University of Zilina. Concretely there is shown the technique how to develop the system of equations for serial kinematic mechanism with 6 degrees of freedom (DOFs). Further this software can be used as universal platform for simulation of mechanisms with serial, parallel as well as hybrid kinematic structure. This flexibility can be considered as a main advantage of the software RoboSim. Its specific feature is that there are used two different methods for calculation of inverse kinematics: heuristic and vector method as well. The versatility, openness and access to the source code create the predisposition for its deployment under the laboratory conditions for controlling of robotic devices developed in authors’ workplace within the last few years.